Burning Table Mountain - Pooley, S. author. aut Link
XI, 315 p.
Keywords: Cape Town's iconic Table Mountain and the surrounding peninsula has been a crucible for attempts to integrate the social and ecological dimensions of wild fire. This environmental history of humans and wildfire outlines these interactions from the practices of Khoikhoi herders to the conflagrations of January 2000. The region's unique, famously diverse fynbos vegetation has been transformed since European colonial settlement, through urbanisation and biological modifications, both intentional (forestry) and unintentional (biological invasions). In all the diverse visions people have formed for Table Mountain, aesthetic and utilitarian, fire has been regarded as a central problem. This book shows how scientific understandings of fire in fynbos developed slowly in the face of strong prejudices. Human impacts were intensified in the twentieth century, which provides the temporal focus for the book. The disjunctures between popular perception, expert knowledge, policy and management are explored, and the book supplements existing short-term scientific data with proxies on fire incidence trends recovered from historical records.